Uma análise bibliométrica da pegada de carbono da computação - Costa, Isadora Magosso da (2023)
This work presents a bibliometric analysis of the relationship between the carbon footprint of Computing and the global CO2 emission indexes. In the past years the planet has suffered the effects of rising global temperature, phenomenon caused mainly by the emission of greenhouse gases into the atmosphere. The Computing field also contributes to this effect, despite this fact being underestimated and not widespread. Based on this assumption, this study collected data from previous related papers and analysed them under the bias of a bibliometric analysis, in order to achieve quantitative results and interpret them under the present context. In conclusion, this study highlighted that researches on the environmental field of Computing remain urgent and relevant, and the ongoing initiatives may not me enough to prevent a potential environmental collapse.